2008
DOI: 10.1111/j.1440-1681.2008.04914.x
|View full text |Cite
|
Sign up to set email alerts
|

CARDIOPROTECTION BY l‐GLUTAMATE DURING POSTISCHAEMIC REPERFUSION: REDUCED INFARCT SIZE AND ENHANCED GLYCOGEN RESYNTHESIS IN A RAT INSULIN‐FREE HEART MODEL

Abstract: 1. Previously, we found that administration of high-dose L-glutamate during postischaemic reperfusion improves haemodynamic recovery and enhances glycogen resynthesis. In the present study, we investigated whether the same effect occurs in an insulin-free model and whether glutamate administration reduces infarct size. Further, we studied whether the cardioprotective effect of glutamate depends on preserved glutamate transamination and K(ATP) channel activity. 2. In a rat isolated, insulin-free, perfused heart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
1

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 30 publications
1
10
1
Order By: Relevance
“…Interestingly, this drop in ATP content was fully counteracted by glutamate administration in the first hour of reoxygenation. In connection with these results, a previous work by Kristiansen and coworkers showed that, in a rat isolated perfused heart model, the administration of exogenous glutamate from the beginning of the reperfusion reduces infarct size to the same extent as its administration during both ischemia and reperfusion, indicating that glutamate main effect is linked to the latter phase 5 . Additionally, we found that the NCX1 inhibitor SN-6 abolished the ability of glutamate to ameliorate ATP production.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Interestingly, this drop in ATP content was fully counteracted by glutamate administration in the first hour of reoxygenation. In connection with these results, a previous work by Kristiansen and coworkers showed that, in a rat isolated perfused heart model, the administration of exogenous glutamate from the beginning of the reperfusion reduces infarct size to the same extent as its administration during both ischemia and reperfusion, indicating that glutamate main effect is linked to the latter phase 5 . Additionally, we found that the NCX1 inhibitor SN-6 abolished the ability of glutamate to ameliorate ATP production.…”
Section: Discussionsupporting
confidence: 60%
“…First, at the concentration tested in this study, glutamate has no evident toxic effect on H9c2 cells and rat adult cardiomyocytes. Second, protection against ischemic injury typically requires glutamate supplementation in the millimolar range 5,6,38,50 . Third, although glutamate has very large muscle/plasma ratios at the baseline, during myocardial ischemia such large concentration gradient dissipates 4 and high exogenous concentrations of glutamate are required to compensate this loss and enable adequate intracellular glutamate loading 6 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The function of glutamate in the heart has been a focus of research since the discovery of its decrease in ischaemia‐reperfusion injury . Many studies have demonstrated that the replenishing of glutamate mitigates myocardial ischaemia‐reperfusion injury, which manifests as attenuated infarcts and improved heart function recovery . Other studies have demonstrated that glutamate did not improve heart function after arrest or significantly decrease 30‐day mortality and myocardial infarcts in patients undergoing heart surgery despite shortening the median intensive care unit stay and decreasing the incidence of severe circulatory failure .…”
Section: Introductionmentioning
confidence: 99%
“…9 Many studies have demonstrated that the replenishing of glutamate mitigates myocardial ischaemia-reperfusion injury, which manifests as attenuated infarcts and improved heart function recovery. [10][11][12] Other studies have demonstrated that glutamate did not improve heart function after arrest or significantly decrease 30-day mortality and myocardial infarcts in patients undergoing heart surgery despite shortening the median intensive care unit stay and decreasing the incidence of severe circulatory failure. 13,14 It is currently accepted that glutamate transporters are a primary cause of the protective effects of glutamate via maintenance of its intracellular content and energy metabolism, [15][16][17][18] which results in improved intracellular Ca 2+ handling.…”
Section: Introductionmentioning
confidence: 99%